Hadith #3559 - Sunan Abi Dawud - Mujahid bin Jabir مجاهد بن جبر; Ubaidullah bin Musa bin Abi al-Mukhtar عبيد الله بن موسى بن أبي المختار باذام; Uthman bin al-'Aswad bin Musa عثمان بن الأسود بن موسى (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone gives something in life-tenancy, it belongs to the one to whom it is given, in his life and after his death; and do not give property to go to the survivor, for if anyone gives something to to to the survivor, it belongs to him.
Grade: Sahih